Distribuição de Na+ e Cl- em plantas jovens de feijão caupi expostas a estresse salino e temperatura elevada - Dutra, Antônia Tathiana Batista (2008)
Although it has many studies on salinity, little is known about the mechanisms of individual Na+ and Cl- in the physiology of plants exposed to salinity. Based on that meant to use this study to evaluate the extent to which the ions Na+ and Cl- are accumulated in different parts of young cowpea [Vigna unguiculata (L.) Walp.] and the possible interference on the steps of perspiration. To prove the hypothesis that the ions present different models of distribution in vegetative parts of cowpea and this process is not affected by temperature. It organized a string surrounding methodological three experiments. Where will I study was to evaluate the distribution of Na+ and Cl- young in parts of cowpea subjected to increasing concentrations of sodium chloride (0, 25, 50, 75 and 100 mM) for 3 days. In what was a greater accumulation of sodium chloride that in all parts studied, except the stem which accumulation in the equivalent proportions. Based on this distribution used with a concentration of 50 mM because it would not exceed the storage capacity and it was possible that a recovery level (it was held for 6 days in NaCl and from the 4th day the samples were divided into two lots. A lot remains NaCl and other exchanges with the solution without NaCl and thus verify that this strategy the plant would be able to recover it. The results corroborated with those obtained in the experiment I except the 1st trifoliate leaves that accumulated more in that Cl. The literature reports that plenty of times in the summer (period of the experiment I), particularly in semi-arid plants accumulate more ions. Where the temperature is a measure of climatic factors that may interfere with the distribution of ions and whether this effect is linked to transpiration. And then we performed the experiment III to assess the combined effect of salinity and high temperatures, in concentrations from 0 to 100 mM NaCl. Exposed to temperatures of 27, 32, 37 and 42 C, separately, during a photoperiod of 12 hours. The results corroborate with those obtained previously in the sodium has focused more on the roots and stems when treated in the last two temperatures. Regarding the chloride ion, was found a behavior similar to previous experiments, as they accumulated in greater proportion in the leaves at temperatures of 32 to 42 C. Notably the accumulation of chloride, is associated withthe amount of water absorbed during the implementation of stress. Regarding transpiration also corroborate the previous results. Thus it appears that regardless of concentration, time, temperature recovery and the ash is more concentrated in the root and stem while chloride is concentrated in the leaves.